Target Coverage and Normal Organ Sparing in Dose-Escalated Total Marrow and Lymphatic Irradiation: A Single-Institution Experience - Han, Chunhui; Liu, An; Wong, Jeffrey Y.C. (Frontiers in Oncology, 2022)
Purpose/Objectives: The aim of this study is to report historical treatment planning experience at our institution for patients receiving total marrow and lymphatic irradiation (TMLI) as part of the conditioning regimen prior to hematopoietic stem cell transplant. Materials/Methods: Based on a review of all historical clinical TMLI treatments plans, we retrieved a 12-Gy cohort of 108 patients with a prescription dose of 12 Gy to the skeletal bones, lymph nodes, spleen, and spinal canal, and retrieved a 20-Gy cohort of 120 patients with an escalated prescription dose of 20 Gy to the skeletal bones, lymph nodes, spleen, and spinal cord, and 12 Gy to the brain and liver. Representative dosimetric parameters including mean and median dose, D80, and D10 (dose covering 80% and 10% of the structure volume, respectively) for targets and normal organs were extracted and compared between the two groups of patients. Results: For the 12-Gy cohort, the average mean dose for normal organs ranged from 18.3 to 78.3% of 12 Gy, and the average median dose ranged from 18.3 to 77.5% of 12 Gy. For the 20-Gy cohort, the average mean dose for normal organs ranged from 13.0 to 76.0% of 20 Gy, and the average median dose ranged from 12.5 to 75.0% of 20 Gy. Compared to the mean dose to normal organs in the 12-Gy cohort, the average mean dose to normal organs increased from 0.0 to 73.1%, with only four normal organs showing a > 50% increase. Normal organ dose in TMLI plans using volumetric modulated arc therapy fields fell within the dose range in historical TMLI plans. Conclusion: Dosimetric data in historical TMLI plans at our institution are summarized at prescription dose levels of 12 Gy and 20 Gy, respectively. Compared to normal organ dose with prescription dose of 12 Gy, the mean and median dose to most normal organs at escalated prescription dose of 20 Gy had an increase less than prescription dose scaling. Dosimetric results from this study can be used as reference data to facilitate clinical implementation of TMLI at other institutions.